ANALYZING THE IMPACT OF WORD OF MOUTH AND EXPERIENCE QUALITY ON SCHOOL CHOICE DECISION THROUGH PERCEIVED VALUE AND BRAND IMAGE - Hanum, Maulia Shofiyah; Rofiaty, Rofiaty; Yuniarinto, Agung (Jurnal Aplikasi Manajemen, 2020)
The objective of this research is to analyze the effect of word of mouth and experience quality on the decision of choosing a school with the mediation of perceived value and brand image. The population of this study is 102 parents who had sent their children to Surya Buana Kindergarten and Playgroup and sent their children to Surya Buana Islamic Elementary School following their graduation, all of which were selected as the sample. This study uses a quantitative approach which is based on research problems and research objective and is categorized as explanatory research. The samples were selected using nonprobability sampling, which means that information retrieval carried out in the population does not have any inherent probability of being chosen as the sample subject. Sampling is limited to certain types of people who can provide the desired information or commonly referred to as Purposive Sampling. The instrument used in this study is questionnaires that were analyzed in SmartPLS 3.0. This study finds that word of mouth and experience quality is insignificant for decision making. However, they are significant for decision making if mediated by perceived value and brand image. Next researches can incorporate variables that influence decision making such as satisfaction, price, demographic variable and other variables to be able to improve strategies in improving decision making in school selection.